Environment Sensitive Polymers For Ophthalmic Drug Delivery - IKHWAN HADI BIN SUHAIME,; MINAKETAN TRIPATHY,; BAKAR ABDUL MAJEED., (International Journal of Pharma and Bio Sciences, 2012)
Environmentally sensitive polymers are smart materials that have gained importance in ophthalmic drug delivery because of their ability to undergo in-situ gelation. This review presents the different polymers used for ophthalmic drug delivery covering the three basic mechanisms of in-situ gelation such as temperature mediated, pH triggered and ion activated in-situ gelation. The characteristics of the polymers, such as physicochemical properties and their pharmaceutical implications in ophthalmic delivery have been discussed exhaustively. This review showed that environmentally sensitive polymers can be utilized for prolonged drug delivery to the eye, because of their long retention time on the ocular surface resulting improved pharmacokinetic profile of the drug molecule.